As mulheres do café em Vitoria da conquista: a dinâmica histórico-espacial da mobilidade do trabalho e a (re)produção da periferia urbana - Lebrão, Jemeffer Souza (2016)
Vitória da Conquista is a city in south-central of Bahia that counts, according to the latest Census of IBGE (2010), with a population of 306,000 people. One of the processes that gave this city its current urban configuration was triggered in the 1970s with the installation and expansion of the coffee agribusiness. Concomitantly, the changes in the form of organization of production and work in the agricultural space, provided the emergency and unprecedented expansion of the urban periphery. The periphery of Vitória da Conquista, understood as a social segregation space, appears in the urban morphology of the city very clearly in the plants in the end of the 1980s. In this research, we approach the territorial dynamics presented from the theoretical perspective of labor mobility. So, we try to identify at the time of the installation of coffee production in the region of the Planalto da Conquista in 1972: a) the relationships and connections between the large number of workers coming from various municipalities of Bahia, and other states of Brazil, who moved seasonally or permanently to Vitória da Conquista to work on coffee plantations and; b) the socio-spatial segregation process that gave rise to different peripheral areas. We are interested in understanding this process with particular attention to the gender composition of the labor force in moving by coffee. Therefore, we present an analysis that allows us, through the memory of the life experiences of the women that work in coffee, understand the processes, actions and practices that occurred in the everyday sphere, in the spatiality of "micro" that allowed and allows nowadays, the reproduction, not only of the social relations of production in the "agro-industrial world of coffee" but of life in the urban periphery of Vitória da Conquista.